Effect of vitamin D supplementation on oral glucose tolerance in individuals with low vitamin D status and increased risk for developing type 2 diabetes (EVIDENCE): A double‐blind, randomized, placebo‐controlled clinical trial. Issue 1 (9th November 2016) - Moreira‐Lucas, Tracy S.; Duncan, Alison M.; Rabasa‐Lhoret, Rémi; Vieth, Reinhold; Gibbs, Alison L.; Badawi, Alaa; Wolever, Thomas M. S.
Abstract : Aims: Low serum 25‐hydroxyvitamin‐D (25(OH)D) concentrations are associated with insulin resistance, β‐cell dysfunction and type 2 diabetes. We conducted a 24‐week double‐blind, randomized, placebo‐controlled trial to examine the effect of 28 000 IU of vitamin D3 once weekly on plasma glucose after a 2 hour‐75 g oral glucose tolerance test (2hrPC glucose), insulin sensitivity and β‐cell function. Study Design and Methods: A total of 71 participants with serum 25(OH)D ≤65 nmol/L, impaired fasting glucose and elevated glycated hemoglobin were randomly assigned to receive 28 000 IU of vitamin D3 (VitD; n = 35) or placebo (n = 36) in cheese once weekly for 24 weeks. The primary outcome was the change in 2hPC glucose. Secondary outcomes were fasting glucose, fasting and postprandial insulin, indices of insulin sensitivity and β–cell function, glycated hemoglobin and lipid profile. Participants underwent an oral glucose tolerance test to determine 2hPC glucose. Results: Mean baseline serum 25(OH)D was 48.1 and 47.6 nmol/L in the VitD and placebo groups, respectively. Serum 25(OH)D significantly increased to 98.7 nmol/L (51 nmol/L increase; P < .0001) in the VitD group. No significant differences in fasting ( P = .42) or 2hPC glucose ( P = .55) or other indices of glucose metabolism, including β‐cell function and insulin sensitivity, were observed between groups. A subgroup analysis of individuals with 25(OH)D < 50 nmol/L and prediabetes did not change these results. The VitD group exhibited a significant reduction in LDL cholesterol (−0.27 vs 0.01 mmol/L, P = .03). Conclusion: Weekly doses of vitamin D3 in individuals with suboptimal vitamin D levels who were at risk for type 2 diabetes did not improve oral glucose tolerance or markers of glycaemic status.